Efectivity of the Open Ended Approach to Increasing Students' Mathematical Creative Thinking Ability in Elementary Schools - Vidanisa Nurkhotimah; Turmudi; Italyani Nurhaifa (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The need for an innovation in learning that must be done by the teacher to achieve the expected learning outcomes. On the other hand, sometimes students do not like mathematics because they find it difficult to determine how to solve a math problem, especially word problems. The ability to think creatively mathematically is needed by students in solving problems. With the Open Ended Approach it is hoped that it can assist students in solving problems so that their mathematical creative abilities will increase. This article aims to conduct a literature review related to the goodness of the open ended approach to improving students' mathematical creative thinking abilities in elementary schools. This study is qualitative and the method used in this research is SLR (Systematic Literature Review). Data collection was carried out by reviewing all articles related to the open ended approach to improving students' mathematical creative thinking abilities in elementary schools which were published in the 2018-2022 period. The articles used in this study were 15 journal articles. Based on this research, it was found that the open ended approach can improve mathematical creative abilities.